PENGEMBANGAN MODEL TECHNO-INDUSTRIAL CLUSTER MINYAK ATSIRI - Noor Fitri; Dadang Mohammad (Asian Journal of Innovation and Entrepreneurship, 2015)
Indonesia is famous as the essential oil of the world. Approximately 90% of patchouli oil supplier world comes from Indonesia. In 2011 Indonesia exported 66742.46 tons of essential oil with a value of 438.16 million US $ (CBS, 2011). But unfortunately, most of the qualities of essential oils from traditional refiners do not meet international standards. During this time improving the quality of essential oil of Indonesia conducted in destination countries. Problems essential oil agro Indonesia still revolves around the continuity of production, production engineering, quality essential oils, and yet essential development of downstream industries. The low price of Indonesian essential oil either because they do not meet quality standards of national / international. This problem can be caused by the process of planting crops that are not essential according to Standard Operating Procedures (SOP) and process technology production is still traditional.Center for the Study Essential Oil Indonesia Islamic University (Center of Essential Oil Studies, CEOs UII) a strong desire to improve the incomes and welfare of farmers and distillers Indonesian essential to develop technology transfer production process international standards, technology transfer purifying essential oils and make essential oils and derivatives as excellence and the pride of Indonesia in the eyes of the world. CEOs UII research focus is to develop the production process technology and improving the quality of Indonesian essential oil seed. Improving the quality of essential oil of international standards can enhance the value of national exports. The problems are expected to be solved by realizing the techno-industrial cluster model of essential oils and the production process of technology transfer and purification of essential oils to the development of derivative products are more economical essential oil according to international standards the European Federation of Essential Oils (EFEO). There are four stakeholders who play a role in the techno-industrial clusters that developed is essential farmers, traditional distillers, CEOs UII, and industry partners. In this techno-industrial cluster, UII CEOs act as a center of excellence in the development and transfer of technology processes Indonesian essential oil production.